Identification of peptide mimotopes of Trypanosoma brucei gambiense variant surface glycoproteins. - Liesbeth Carolien Van Nieuwenhove; Stijn Rogé; Fatima Balharbi; Tessa Dieltjens; Thierry Laurent; Yves Guisez; Philippe Büscher; Veerle Lejon (Public Library of Science (PLoS), 2011)
BACKGROUND: The current antibody detection tests for the diagnosis of gambiense human African trypanosomiasis (HAT) are based on native variant surface glycoproteins (VSGs) of Trypanosoma brucei (T.b.) gambiense. These native VSGs are difficult to produce, and contain non-specific epitopes that may cause cross-reactions. We aimed to identify mimotopic peptides for epitopes of T.b. gambiense VSGs that, when produced synthetically, can replace the native proteins in antibody detection tests. METHODOLOGY/PRINCIPAL FINDINGS: PhD.-12 and PhD.-C7C phage display peptide libraries were screened with mouse monoclonal antibodies against the predominant VSGs LiTat 1.3 and LiTat 1.5 of T.b. gambiense. Thirty seven different peptide sequences corresponding to a linear LiTat 1.5 VSG epitope and 17 sequences corresponding to a discontinuous LiTat 1.3 VSG epitope were identified. Seventeen of 22 synthetic peptides inhibited the binding of their homologous monoclonal to VSG LiTat 1.5 or LiTat 1.3. Binding of these monoclonal antibodies to respectively six and three synthetic mimotopic peptides of LiTat 1.5 and LiTat 1.3 was significantly inhibited by HAT sera (p<0.05). CONCLUSIONS/SIGNIFICANCE: We successfully identified peptides that mimic epitopes on the native trypanosomal VSGs LiTat 1.5 and LiTat 1.3. These mimotopes might have potential for the diagnosis of human African trypanosomiasis but require further evaluation and testing with a large panel of HAT positive and negative sera.